1-D transient numerical modeling of counter-current two-phase stratified flow inside a medium temperature solar linear collector. (1st January 2018) - López, R.; Lecuona, A.; Ventas, R.; Nogueira, J.
Graphical abstract: Highlights: A 1-D solar collector model with counter-current gravity stratified flow has been developed. The model is relevant for direct steam production (DSP) under transient conditions. The algorithm ensures high accuracy for rapid phase change events. The model allows studying angular radiation gradients phenomena. Abstract: Two-phase gravity-driven and gravity-stratified flow regime inside a pipe, which is present in many engineering applications, is an attractive option for solar cooling/heating/power production using Rankine cycles, absorption cycles or any other thermodynamic application by means of vapor as working fluid. This paper offers a numerical model of this flow configuration that copes with transient phenomena, like unsteadiness of solar radiation, among others. The mathematical model consists of 1-D balance equations for mass and momentum for both fluids and energy for both fluids and the wall of the pipe that absorbs the solar radiation. The model is characterized by the fact that the area (or height) of the liquid layer is treated as a dependent variable forming part of the solution. The numerical method consists in a finite volume staggered grid discretization of the governing equations. Mass flow and liquid area are calculated with a semi-implicit pressure based method and the transient terms are treated with the explicit first stage singly implicit Runge-Kutta (ESDIRK) method. The calculation of the mass transfer rate from liquid to vapor is calculated iteratively by a guess-and-correct mass transfer algorithm, specially developed for stratified flows. The results show the applicability and benefits of this model for the not so well known counter-current stratified two-phase with evaporation/boiling. Additionally, the performance of the mass transfer algorithm is discussed showing that it is monotonic decreasing and linearly convergent.